Tailoring M7C3 carbide via electron work function-guided modification. (1st January 2021) - Guo, Liqiu; Tang, Yunqing; Cui, Juan; Li, Jiaqi; Yang, Jer-Ren; Li, D.Y.
Abstract: M7 C3 carbide [M: metallic element] is the primary reinforcement in white cast irons. Further improving its properties for maximized benefits is highly desired. However, no clear clues are available to guide the modification. Through atomic force microscopy in-situ analysis and first-principles calculations, we demonstrate that (Fe, Cr)7 C3 carbide's strength is governed by its metallic bond component. We theoretically prove that M7 C3 carbide is tailorable by partially replacing its metallic elements with substitutes selected based on their work function as an indicator. This study provides an insight into the electronic origin of carbide's mechanical behaviour, helping guide developing high-performance M7 C3 carbides. Graphical abstract: Image, graphical abstract